Peluang dan Tantangan Fintech Syariah dalam Mendorong Perekonomian UMKM Masyarakat Kediri - Pinky Sutan Efendi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The development of technology will have a direct impact on aspects of people's economic life. The emergence of sharia-based financial technology makes it easy to get the desired funds with a short time and easy process. Technological advances marked by the phenomenon of innovation create a new market that also encourages the growth of fintech in the financial services industry. Fintech itself is not new to the financial services industry. The development of fintech in Indonesia is emerging with a new model, namely sharia-based fintech. The service is an online lending and borrowing product that applies adjustments to sharia principles, where there is a certain profit to be obtained without anything less at any cost, then in terms of funding in sharia fintech, there is no determination of interest from the lender, because everything is determined through a contract that has been agreed from the start. Islamic fintech is an inseparable part of the national fintech industry which also participates in encouraging the growth of MSMEs in Indonesia. Solutions in terms of difficulties for development in MSME businesses in terms of capital financing can be done through fintech. For business people, especially MSMEs, fintech can help to get convenience in the financial area.